Vegetation assessment of native tree species in Broussonetia papyrifera‐dominated degraded forest landscape in southern Ghana. Issue 3 (13th June 2016) - Agyeman, Victor K.; Addo‐Danso, Shalom D.; Kyereh, Boateng; Abebrese, Isaac K.
Abstract: Question: Does the invasive tree species Broussonetia papyrifera facilitate the natural regeneration of native tree species in a degraded tropical forest landscape? Location: Afram Headwaters Forest Reserve, southern Ghana. Methods: We established sampling areas and assessed seedlings and saplings <5 cm DBH in nine habitats. The habitats were logging road, skid trail, large canopy gaps dominated by B. papyrifera, large canopy gaps dominated by invasive Chromolaena odorata, Nauclea diderrichii plantation, Mansonia altissima plantation, Terminalia ivorensis plantation, abandoned farmland and unlogged forest. Results: We found that the abundance of pioneers declined with increasing abundance of B. papyrifera . This trend was more pronounced in the farmland and in the N. diderrichii plantation. By contrast, increased abundance of B. papyrifera did not lead to a decrease in the abundance of the shade‐tolerant species. B. papyrifera seedlings and saplings were absent in the forest understorey. We also found a lower abundance and richness of some vulnerable tree species and valuable timber species in the N. diderrichii plantation and in gaps dominated by B. papyrifera . However, we recorded both shade‐tolerant and shade‐intolerant species in the gaps dominated by B. papyrifera . Conclusions: We found both shade‐tolerant and shade‐intolerant species in the B. papyrifera ‐dominated gaps. This can provide a basis for future studies to explore the potential of such tree species in restoration programmes targeted at B. papyrifera ‐invaded sites. Our results also suggest that the integrity of the undisturbed forest patches in the landscape must be protected to help prevent B. papyrifera from spreading further. We suggest further studies should be conducted at replicated sites with a similar habitat that represent varying levels of invasion by  B. papyrifera to draw conclusions regarding the species' potential to facilitate regeneration of native tree species. Abstract : We assessed the potential of Broussonetia papyrifera, an invasive tree species, to facilitate natural regeneration of native tree species. The abundance of native pioneers declined with increasing abundance of B. papyrifera . We found both shade‐tolerant and shade‐intolerant species in habitat dominated by B. papyrifera . The integrity of undisturbed forest patches should be protected to reduce the spread of B. papyrifera .